A controlled study of personality traits in female adolescents with eating disorders. (14th May 2013) - Liley, Lois J.; Watson, Hunna J.; Seah, Elizabeth; Priddis, Lynn E.; Kane, Robert T.
Abstract Background Among adults, personality traits have been implicated in the development and maintenance of eating disorders (EDs); whether these findings extend to youth is unknown. The aim of this study was to investigate personality traits of adolescents with EDs. Methods A case‐control approach was performed by comparing a clinical group of female adolescents with EDs (n = 23) to a control group of adolescents in the general community (n = 26) on personality traits of inhibited, self‐demeaning, and borderline tendency. Controls were frequency‐matched to cases on age and sex, were drawn from a similar geographic catchment area, and observed in the same year as clinical cases. Results The clinical group demonstrated significantly higher scores on self‐demeaning (F(1, 47) = 41.39, p < .001, η2 = .075), borderline (F(1, 47) = 24.50, p < .001, η2 = .093), and inhibited (F(1, 47) = 13.33, p = .001, η2 = .014) personality styles. Adjustment for affective symptomatology diminished the strength of these relationships, but personality pathology still demarcated the group with clinical EDs. Conclusions The well‐established link between personality pathology and EDs in adults generalised to adolescents.